OEE Evaluation Shows 68 Percent Machine Productivity Level: Evaluasi OEE Menunjukkan Tingkat Produktivitas Mesin Sebesar 68 Persen - Putra S, M. Reyvaldo; Putra, Boy Isma (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Productivity and machine effectiveness are critical factors in manufacturing systems to ensure product quality and operational efficiency. Specific Background: In PVC pipe production, machine downtime and performance issues often reduce overall productivity levels. Knowledge Gap: Limited integration of Overall Equipment Effectiveness and Failure Mode and Effect Analysis is applied to identify root causes and prioritize improvements in machine performance. Aims: This study aims to evaluate machine productivity using OEE and determine improvement priorities using FMEA in a PVC pipe production process. Results: The analysis shows an average availability of 91%, performance rate of 80%, and quality rate of 93%, resulting in an OEE value of 68%, which is below the ideal standard of 85%. The main causes of low effectiveness are related to downtime factors such as pipe defects, machine instability, and operator-related issues. FMEA analysis identifies priority improvements with the highest Risk Priority Number of 648, followed by 392 and 378. Novelty: The study combines OEE and FMEA to provide a structured evaluation of machine productivity and prioritized corrective actions. Implications: The findings offer practical guidance for improving machine performance and reducing downtime in manufacturing operations. Keywords: Machine Productivity, OEE Analysis, FMEA Method, Downtime Factors, Manufacturing System Key Findings Highlights Combined metrics revealed suboptimal operational performance below standard threshold Root cause mapping identified dominant sources of production interruption Risk prioritization guided targeted corrective action planning